2013
DOI: 10.2166/wst.2013.381
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of green roof substrate detention characteristics

Abstract: Green roofs may make an important contribution to urban stormwater management. Rainfall-runoff models are required to evaluate green roof responses configuration, with the substrate or growing media providing both retention and detention of rainfall. The objective of the research described here is to quantify the detention effects due to green roof substrates, and to propose a suitable hydrological modelling approach.Laboratory results from experimental detention tests on green roof substrates are presented. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 10 publications
3
44
0
Order By: Relevance
“…1 for event 7. Overall values of k ranged from 0.003 to 0.065; such results are similar in magnitude to other published outcomes [1,4]. The mean values of k for each year of study showed a year-on-year increase.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…1 for event 7. Overall values of k ranged from 0.003 to 0.065; such results are similar in magnitude to other published outcomes [1,4]. The mean values of k for each year of study showed a year-on-year increase.…”
Section: Resultssupporting
confidence: 85%
“…Rainfall simulations conducted at two different rainfall intensities found that k decreased with increased intensity [4], however no significant correlation was seen in the 25 event dataset This indicates that the changes in k over time are not due to differing distributions of rainfall events between years.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Increasing media depths have been found to increase detention with prolonged runoff, higher peak attenuation and longer peak lag times [16][17][18][19], due to longer vertical transport distances. Others have not found this to be significant and have emphasized the importance of the horizontal flow path to the gutter and physical resistance in the drainage layer for observed detention performance [20,21].…”
Section: Green Roof Configuration and Geometrymentioning
confidence: 99%
“…It should be noted that the focus here is specifically on retention performance (i.e. volumetric control); detention (temporal delay) is addressed separately (see for example, Jarrett and Berghage, 2008; Kasmin et al, 2010;Yio et al, 2012;Vesuviano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%